A model for technology diffusion determines productivity distribution and aggregate growth - Kumar, Manoj (Productivity : A Quarterly Journal of The National Productivity Council)
This paper studies how technology diffusion interacts to endogenously determine the productivity distribution and generate aggregate growth. This paper models firms that choose to adopt technology, or produce with their existing technology. In the context of technology diffusion, one therefore has to consider whether redistributive revenues of the government may, in fact, be allocated towards reducing the fixed costs associated with productive technologies. This paper presents a model in which the cost of technology diffusion is endogenous and varies across heterogeneous firms. The results indicate that the technology with low productivity is used by the majority of individuals in the early stages of development. At this stage, the income distribution is characterized by a relatively higher level of inequality. As capital deepening and redistribution of income and wealth takes place, the inequality among individuals tends to decrease. Once this happens, individuals prefer a relatively larger proportion of government revenue to be allocated towards cost-reducing Research and Development (R&D) expenditures. Eventually, all individuals make the switch to better technology and consequently their incomes converge. - Reproduced
Keywords: India - Economic policy, India - Commercial policy, Industrial policy - India, Technology diffusion